2008
DOI: 10.1002/andp.200710276
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control in flashing ratchets

Abstract: In honour of Max Planck (1858Planck ( -1947 on the occasion of his 150th birthday.A flashing ratchet uses a time-dependent, spatially periodic, asymmetric potential to rectify thermal motion of Brownian particles. Here we review approaches to improve the particle flux in this type of Brownian motor by feedback strategies that switch the potential based on the instantaneous particle distribution. We review strategies that are based on the force experienced by the particles, and introduce a new feedback strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(75 citation statements)
references
References 38 publications
1
72
2
Order By: Relevance
“…This is different from earlier studies based on the Langevin equation (see, e.g., [10,19,30]), where the feedback is applied directly to the position of one particle, χ i (t), or to the average of N particle positions…”
Section: Transport Mechanismmentioning
confidence: 68%
See 2 more Smart Citations
“…This is different from earlier studies based on the Langevin equation (see, e.g., [10,19,30]), where the feedback is applied directly to the position of one particle, χ i (t), or to the average of N particle positions…”
Section: Transport Mechanismmentioning
confidence: 68%
“…(4) on sees that the feedback force changes its sign whenever the delayed mean particle positionz(t−τ D ) becomes smaller or larger than z 0 ; we therefore call z 0 the "switching" position. Our ansatz is partially motivated by an earlier (Langevin equation based) study of Craig et al [19] on feedback control of a flashing ratchet via the so-called "maximum-displacement strategy". In that study, the fixed position z 0 was identified with the mean particle position of the uncontrolled system [i.e., F fc (t) = 0] at t → ∞, that is, the equilibrium positionz eq = dzzρ eq (z), where…”
Section: Definition Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) We have focused here on proving an upper bound for the particle flux because this quantity can readily be measured in experimental realizations of feedback ratchets [17]. In a recent paper [19], written after the present one, an analogous upper bound was derived for the power output of a feedback ratchet, based on the results and techniques presented here.…”
Section: Discussionmentioning
confidence: 94%
“…Using the results presented here, they obtain that no more than 95% of the maximum gain achieved by the feedback strategy can be observed for that real system. The experimental realization of this system is currently under way [17]. (4) In general, the flux generated by the open-loop ratchet is much smaller than the flux generated by the feedback ratchet [6].…”
Section: Discussionmentioning
confidence: 99%